Advocates of humanity : human rights NGOs in international criminal justice - Lohne, Kjersti (Oxford : Oxford University Press, 2020)
This volume analyses the cultural meaning and social dynamics of international criminal justice by exploring the role of human rights organisations in this sphere after the creation of the International Criminal Court. The text offers an analysis of punishment 'gone global', and how it is constituted by and of global relations of power.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 10, 2020).
Keywords: Non-governmental organizations -- Law and legislation; Non-governmental organizations -- International cooperation; International agencies -- Law and legislation; International Criminal Court; Human rights advocacy; International criminal law; Law; International law